Impact of sociodemographic characteristics and drug-related side effects on quality of life of patients with hepatocellular carcinoma receiving sorafenib treatment in Iraqi hospitals - H. Qasim , Tuqa; J. Ibraheem, Mazin; Jabarah, Mohammed Abdul- Hassan (Journal of the Faculty of Medicine Baghdad, 2023)
Background: Sorafenib is an oral multikinase inhibitor which has been given approval by the United States Food and Drug Administration for the treatment of patients diagnosed with hepatocellular carcinoma and advanced renal cell carcinoma . However, measuring quality of life and patient-reported symptoms may provide further information for evaluating and comparing treatment efficacy and toxicity profiles during cancer treatment. Despite the critical importance of patients’ quality of life while receiving anticancer treatment, neither Iraqi patients undergoing anti-cancer medications in general nor those receiving Sorafenib in particular had any published data evaluating this important parameter. Objectives: The study aimed to assess the quality of life of Sorafenib-treated Iraqi patients diagnosed with hepatocellular carcinoma. Methods: A prospective, cross-sectional study was performed at the oncology clinic of (Oncology Teaching Hospital, Al-Amal Hospital and Al -Imamein Al- Kadhimein Medical City in Baghdad, Iraq) during the period from November 2021 to July 2022. Patients were enrolled in current study by using a convenient sampling method. Assessment of quality of life was performed using a questionnaire from the “European Organization for Research and Treatment of Cancer”. Statistical analyses were performed using statistical package for Social Sciences. Student’s t-test and ANOVA test were used to compare categorical data. P value of <0.05 was considered statistically significant. Results: The present study included 52 patients in total. Of the latter, 90.4% experienced fatigue, making it the most frequent adverse event, followed by anorexia, anemia, nausea, diarrhea and vomiting (71.2%, 67.3%, 65.4%, 59.6%, 26.9%, respectively). In spite of that, some participants had a good quality of life while others did not. Conclusion: Patients with hepatocellular carcinoma on sorafenib treatment have variable quality of the life. The latter is significantly affected by patients’ sociodemographic characteristics and treatment-related adverse events.